Nias Marriage at Ehomo Village, Mazo Sub-District, South Nias District Analyzed through Indonesian Marriage Regulations - Panjaitan, Bernat; Nasution, Ade Parlaungan; Siahaan, Nimrot (International Journal Labs, 2022)
Background: The large number of marriage dowries that apply in nias tribal marriage customs becomes one of the considerations for nias people to hold a wedding therefore holding marriages in other areas (outside nias area), especially in urban areas, become one of the options for nias people to avoid the large cost of dowry that must be given by men to the female side. Mahar in Nias custom also contains issues of gender injustice. Aim: This article aimed to study the marriage status of those who get married in Ehomo Village and how it is viewed through Law No. 1 of 1974 concerning Marriage. Method: This type of research in the preparation of law is empirical legal research. Presearch law taken from the facts that exist in a society, legal entity or government body, so that the material isthen compiled systematically, studied then drawn conclusions in relation to the issues studied, namely regarding the marriage of indigenous Nias tribes reviewed from Law number 1 of 1974 on marriage in Ehomo Village Maze District of South Nias Regency. Findings: The magnitude of dowry in Nias especially in Tetegawa'ai Ehomo is driven by wedding events that every stage should be celebrated with a massive event. One stage can be up to several days, so for a marriage can take a week. To finance this event, it is not uncommon for men to think about it or take responsibility.